Developing cetacean-friendly guidelines, from whale watching to offshore wind farm operation - Chen, Yu-Ju; Lee, Pey-Yi (Frontiers in Marine Science, 2023)
Developing offshore wind farms may impact cetaceans, i.e., vessel collisions and underwater noise.Therefore, it is critical to protect cetaceans while developing offshore wind farms. We first studied the code of conduct/guidelines for whale watching and then interviewed the local whale-watching industry to learn about the interaction between cetaceans and vessels. After that, we compared current whale-watching guidelines in Taiwan with 69 published guidelines from other countries and locations, then developed the guideline for the offshore wind farm industry. The results showed that rules related to approaching and interacting with cetaceans in Taiwan are similar to those in other countries. However, restrictions on swimming with cetaceans and approaching calves are prohibited in Taiwan. From the survey of the whale-watching industry, most whale-watching guidelines in Taiwan were feasible, and the guideline should be described in the premise with different phenotypic traits of various cetaceans. Based on the whale-watching guideline, we developed the code of conduct for protecting cetaceans from the impact of vessels, specifically in offshore wind farm operations in Taiwan.There are rich biotic and abiotic ocean resources in Taiwan. It is important to use them wisely when there is an encounter between an ambitious policy for quick developing ocean resources, such as offshore wind farms. To mitigate the impact on cetaceans, we need to improve the practice of selfgovernance and then figure out a cetacean-friendly guideline for offshore wind farm operation. The whale-watching has been practice for over 20 years in Taiwan. This industry has much experience in interactions between vessels and cetaceans and already has a guideline built with operators' opinions.Besides applying these experiences to the industry of offshore wind farms, we follow the spirit that is adapting the guideline by surveying the opinions of operators of offshore wind farms over time.Moreover, we hope these ideas can also be expanded to other marine related industries in Taiwan in the future.